Prescription of Systemic Steroids for Acute Respiratory Infections in Korean Outpatient Settings: Overall Patterns and Effects of the Prescription Appropriateness Evaluation Policy - Taejae Kim; Young Kyung Do (Korean Society for Preventive Medicine, 2020)
Objectives The objective of this study was to identify individual and institutional factors associated with the prescription of systemic steroids in patients with acute respiratory infections and to investigate the role of a policy measure aimed to reduce inappropriate prescriptions. Methods We used data from the National Health Insurance Service-National Sample Cohort from 2006 to 2015 and focused on episodes of acute respiratory infection. Descriptive analysis and multiple logistic regression analysis were performed to identify individual-level and institution-level factors associated with the prescription of systemic steroids. In addition, steroid prescription rates were compared with antibiotic prescription rates to assess their serial trends in relation to Health Insurance Review and Assessment Service (HIRA) Prescription Appropriateness Evaluation policy. Results Among a total of 9 460 552 episodes of respiratory infection, the steroid prescription rate was 6.8%. Defined daily doses/1000 persons/d of steroid increased gradually until 2009, but rose sharply since 2010. The steroid prescription rate was higher among ear, nose and throat specialties (13.0%) than other specialties, and in hospitals (8.0%) than in tertiary hospitals (3.0%) and other types of institutions. Following a prolonged reduction in the steroid prescription rate, this rate increased since the HIRA Prescription Appropriateness Evaluation dropped steroids from its list of evaluation items in 2009. Such a trend reversal was not observed for the prescription rate of antibiotics, which continue to be on the HIRA Prescription Appropriateness Evaluation list. Conclusions Specialty and type of institution are important correlates of steroid prescriptions in cases of acute respiratory infection. Steroid prescriptions can also be influenced by policy measures, such as the HIRA Prescription Appropriateness Evaluation policy.